Advances and novel developments in mechanisms of allergic inflammation - Han, Xiaorui; Krempski, James W.; Nadeau, Kari (Allergy (Copenhagen), 2020)
In the past decade, research in the molecular and cellular underpinnings of basic and clinical immunology has significantly advanced our understanding of allergic disorders, allowing scientists and clinicians to diagnose and treat disorders such as asthma, allergic and nonallergic rhinitis, and food allergy. In this review, we discuss several significant recent developments in basic and clinical research as well as important future research directions in allergic inflammation. Certain key regulatory cytokines, genes and molecules have recently been shown to play key roles in allergic disorders. For example, interleukin‐33 (IL‐33) plays an important role in refractory disorders such as asthma, allergic rhinitis and food allergy, mainly by inducing T helper (Th) 2 immune responses and clinical trials with IL‐33 inhibitors are underway in food allergy. We discuss interleukin 4 receptor pathways, which recently have been shown to play a critical role among the allergic inflammatory pathways that drive allergic disorders and pathogenesis. Further, the cytokine thymic stromal lymphopoietin (TSLP) has recently been shown as a factor in maintaining immune homeostasis and regulating type 2 inflammatory responses at mucosal barriers in allergic inflammation and targeting TSLP‐mediated signalling is considered an attractive therapeutic strategy. In addition, new findings establish an important T cell–intrinsic role of mucosa‐associated lymphoid tissue lymphoma translocation protein 1 (MALT1) proteolytic activity in the suppression of autoimmune responses. We have seen how mutations in the filaggrin gene are a significant risk factor for allergic diseases such as atopic dermatitis, asthma, allergic rhinitis, food allergy, contact allergy, and hand eczema. We are only beginning to understand the mechanisms by which the human microbiota may be regulating the immune system, and how sudden changes in the composition of the microbiota may have profound effects, linked with an increased risk of developing chronic inflammatory disorders, including allergies. New research has shown the important but complex role monocytes play in disorders such as food allergies. Finally, we discuss some of the new directions of research in this area, particularly the important use of biologicals in oral immunotherapy, advances in gene therapy, multifood therapy, novel diagnostics in diagnosing allergic disorders and the central role that omics play in creating molecular signatures and biomarkers of allergic disorders such as food allergy. Such exciting new developments and advances have significantly moved forth our ability to understand the mechanisms underlying allergic diseases for improved patient care.